Influence Of Prostaglandin F2α On Preservability Of Jamunapari Buck Semen - Pankaj, Gautam Kr; Chaudhary, S.K.; Pandey, R.P.; KR , Sanjiv (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
One hundred and forty four ejaculates were collected in artificial vagina from six Jamunapari bucks. After collection semen samples were split-diluted in EYC without (control) and with prostaglandin F2α @ 4 µg/ml (treated) and stored at 4°C up to 72 hrs. The seminal characteristics, i.e. progressive motility, live sperm percentage, and abnormal percentages of acrosome, head and tail were evaluated at 72 hourly intervals. There were significant differences between control and prostaglandin F2α treated samples for sperm motility, viability and head abnormality percentages at 24, 48 and 72 hrs of preservation. Prostaglandin F2α was found to be good additive in terms of progressive motility, live sperm percentage, and sperm tail and acrosomal abnormality percentage and hence may be used in routine refrigeration preservation of buck semen.
Keywords: Jamunapari bucks; PGF2α; Progressive motility; Live sperm percentage; Head; Tail and Acrosomal abnormality percentage